1996
DOI: 10.1128/mcb.16.12.6644
|View full text |Cite
|
Sign up to set email alerts
|

ZBP-89, a Krüppel-Like Zinc Finger Protein, Inhibits Epidermal Growth Factor Induction of the Gastrin Promoter

Abstract: We have shown previously that a GC-rich element (GGGGCGGGGTGGGGGG) conferring epidermal growth factor (EGF) responsiveness to the human gastrin promoter binds Sp1 and additional undefined complexes. A rat GH4 cell line expression library was screened by using a multimer of the gastrin EGF response element, and three overlapping cDNA clones were identified. The full-length rat cDNA encoded an 89-kDa zinc finger protein (ZBP-89) that was 89% identical to a 49-kDa human factor, ht(beta), that binds a GTGGG/CACCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(167 citation statements)
references
References 39 publications
7
156
1
3
Order By: Relevance
“…16 Monoclonal antibodies against phospho-ERK1/2, phospho-p38, phospho-JNK1/2, phospho-Elk1, phospho-ATF2 and caspase-8, and polyclonal antibodies against ERK1/2, p38, JNK, c-Jun, phospho-c-Jun, cleaved PARP, caspase-3, cleaved caspase-3, caspase-9, cleaved caspase-9 and Bid were obtained from Cell Signaling (Beverly, MA, USA). The monoclonal Flag M2 antibody was purchased from Sigma (St Louis, MO, USA).…”
Section: Antibodies and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Monoclonal antibodies against phospho-ERK1/2, phospho-p38, phospho-JNK1/2, phospho-Elk1, phospho-ATF2 and caspase-8, and polyclonal antibodies against ERK1/2, p38, JNK, c-Jun, phospho-c-Jun, cleaved PARP, caspase-3, cleaved caspase-3, caspase-9, cleaved caspase-9 and Bid were obtained from Cell Signaling (Beverly, MA, USA). The monoclonal Flag M2 antibody was purchased from Sigma (St Louis, MO, USA).…”
Section: Antibodies and Chemicalsmentioning
confidence: 99%
“…6,14,15 ZBP-89 (ZNF148, Zfp148) is a Krü ppel-type zinc-finger protein that is ubiquitously expressed. 16 Recent studies have revealed that ZBP-89 possesses multiple functions, including transcriptional regulation of a variety of genes, 17 cell growth arrest 18,19 and cell death. 18 ZBP-89 expression is highest at the villus tip where apoptotic mature enterocytes are sloughed into the lumen.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] ZNF148 is universally expressed at low levels in most tissues, 8 including those in the gastrointestinal tract. 9 ZNF148 is a multifunctional transcription factor associated with signaling pathways upstream of cellular proliferation, embryogenesis, differentiation, growth arrest, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mt␤ (identical to BFCOL1, BERF-1) and its human and rat homologues (ht␤, ZBP-89, ZFP148) are reported to bind regulatory regions of various genes, such as the V␤8.1 promoter and the V␣ silencer of the T-cell receptor genes (17), the gastrin promoter (29), the type I collagen promoter (27), the ␤-enolase enhancer (28), the ornithine decarboxylase promoter (30), the p21WAF1 promoter (31), the matrix metalloproteinase-3 promoter (32), the pT␣ enhancer (33), and the silencer element of the vimentin gene (34). Our data showing that mt␤ is ubiquitously expressed at both mRNA and protein levels are consistent with previously published reports and the fact that mt␤ functions in the various promoters and enhancers in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…During this study, several cDNAs that have identical sequences with mt␤ have been reported: BFCOL1 that binds to the proximal promoters of the type I collagen genes (27) and BERF-1, a 89-kDa protein that binds to a muscle-specific enhancer of the ␤-enolase gene (28). In addition, the rat and human homologue of the protein, ZBP-89, has been shown to bind to promoter regions of the gastrin gene (29) and the ornithine decarboxylase promoter (30). It has subsequently been reported that the same zinc finger protein also binds to the p21WAF1 gene (31), the matrix metalloproteinase-3 gene (32), the pT␣ gene (33), and the vimentin gene (34).…”
Section: Identification Of a Nuclear Protein Binding To The Lck Proximalmentioning
confidence: 99%